School-university partnerships in action - Day, Christopher; Gu, Qing; Townsend, Andrew; Holdich, Catherine (CRC Press, 2021)
"This book provides new knowledge, insights and experience about school-university partnerships. Drawing upon evidence from international research of the world's most improved systems, and learning from a UK research council funded 'knowledge exchange' project, it reveals that when the profound differences between the practice worlds of schools and the theoretical worlds of university academics are embraced and cherished, rather than eschewed, school-university partnerships become exciting avenues of learning which connect, challenge and transform the thinking and practice of all those involved. Over its eight chapters, the book explores uncertainties, challenges and possibilities faced by those who seek to create, develop and sustain school-university partnerships that aspire to improve the practice and understanding of the leadership of teaching and learning in schools. It explicates and elucidates precepts, principles and practices for achieving such successful partnerships between higher education and school leaders, and contextualises these in terms of policy wide developments internationally. This book will appeal to school leaders internationally, leadership training organisations, and academics who lead post-graduate leadership and management programmes"--
The rise of school-university partnerships : changing circumstances, changing roles -- Successful partnerships : opportunities and outcomes -- Research and development as a shared endeavour -- An exemplar project : working with schools serving high need communities -- Building and sustaining critical friendships -- Schools on the front line : principals as curators of professional learning -- From relational connectedness to trustful collaboration -- The promise of change.
Keywords: College-school cooperation; Educational leadership; School principals